LINC-12. Encouraging early outcomes with image guided pencil beam proton therapy for cranio-spinal irradiation and unique considerations for paediatric population – First report from India. (3rd June 2022) - Gaikwad, Utpal; Sudarsan, Rishan Thimma; Noufal, M P; Jacinthlyn, Sylvia; Reddy, Ashok K; Panda, Pankaj Kumar; Chilukuri, Srinivas; Sharma, Dayananda; Jalali, Rakesh
Abstract: BACKGROUND: To report our experience with image guided pencil beam proton beam therapy (PBT) for craniospinal irradiation (CSI). MATERIALS AND METHODS: Between January 2019 to Dec 2021, we carried out a detailed audit of the first forty patients treated with PBT. All patients were carefully selected after approval from our institutional multidisciplinary tumour and proton board meetings. Median age of the patient cohort was 8 years, and histologies include 20 medulloblastoma, 7 recurrent ependymoma, 3 pineoblastoma, 3 were germ cell tumors and remaining 7 constituted other diagnoses. Forty percent patients received concurrent chemotherapy. We had recorded acute toxicities on a prospectively maintained database. We also report early outcomes in this cohort and discuss limitations of current contouring guidelines during CSI PBT planning. RESULTS: Median CSI dose was 23.4 GyE (Gray Equivalent; range 21.6 - 35). Thirty-five patients (87.5%) completed their CSI without interruption as an outpatient procedure. Five patients required hospital admission during treatment, while one developed grade 3 mucosal toxicity, requiring plan adaptation and treatment break. No patient had grade 2 or more weight loss during the treatment. Forty-five percent (18) developed grade 1 hematological toxicities and 20% (8) developed grade 2 or 3 toxicities; none had grade 4 toxicities. At median follow up of 12 months, 90 % patients are alive of whom 88.9 % are having local control. Special consideration with modification in standard contouring used at our institute helped in limiting acute toxicities in paediatric CSI patients. CONCLUSION: Our preliminary experience with modern contemporary PBT using pencil beam technology and daily image guidance in a range of tumours suitable for CSI is encouraging. Patients tolerated the treatment well with acceptable acute toxicity and expected short-term survival outcome. In paediatric CSI patients, modification in standard contouring guidelines required to achieve better results with PBT